Regenerative beam extraction on the Buenos Aires Synchrocyclotron - Mayo, Santos; Heras, Carlos A.; Rosenblatt, Jorge (North Holland Publishing, 1958)
Fil: Mayo, Santos Comisión Nacional de Energía Atómica; Argentina